Análise ecotoxicológica da acrilamida utilizando uma microalga como organismo indicador - Nunes, Bárbara Werle (2014)
Acrylamide is a water soluble monomer with a multitude of industrial and chemical applications. In polymeric form, which is also known as polyacrylamide, it may be used as a flocculant for water treatment. However, this monomer presents carcinogenic risk and it can cause changes in the endocrine system of living beings, it is also called endocrine disrupter. On the Ordinance of the Ministry of Health 2914/2011, it was established a maximum limit of 0.5 micrograms/L acrylamide for drinking water. However, there is no evidence in the literature on the detection of acrylamide in the drinking water. Thus, the study of the behavior of acrylamide as an environmental contaminant and carcinogen is of a great value to the public health. Thus, the main objective of this study was the analysis of the expected changes toxicology of acrylamide in different concentrations, using green algae as indicator organisms. The study was conducted through the following steps: (I) The structure of a study methodology, based on the references that are available and adapted for a consistent routine of work with the good laboratory conditions of the institution; (II) the performance of the ecotoxicological tests with algae, which are treated with polyacrylamide solution used in the municipality of Santa Maria Water Treatment Station - RS; (III) the performance of ecotoxicological tests with algae, treated with different concentrations of acrylamide; (Iv) the calculation of the sample cell biovolume (V) the analysis of chlorophyll "a" and (VI)the statistical analysis of the results and interpretation of the data of the research. The experiments were performed in the laboratory of sanitation- Lasam, from the Federal University of Santa Maria - UFSM from February to August 2014. The results demonstrated that it was possible to develop the ecotoxicological study with polyacrylamide, because it is a commercial substance that has no analytical purity, which led to no regular results, making it impossible to reproduce the tests. However, in the ecotoxicological analysis of acrylamide, the acrylamide results indicated that significantly inhibited the growth of algae, yielding 5.88 mg/L-1 as the concentration which inhibited 50% of the growth of the algal cells. Both the microscopic cell counting as the dosage of chlorophyll "a" was effective in the experimental biomass quantification. The most important outcome of the work consist in assessing changes in cell biovolume and phenotypic plasticity of the species D. quadricauda unprecedentedly parameters evaluated for exposure to acrylamide. The use of calculation of biovolume combined with cell counts proved quite useful for analyzing the results, showing the variation in cell size during the experiment. Phenotypic plasticity of gender has changed with exposure to acrylamide, which gives an important finding in the evaluation of toxicity.